Protein supplementation for cows wintered on milo stubble - M. McKee; K. Kimole; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1978)
Cows in mid-to-late gestation gained significantly (P<.05) more while grazing milo stover supplemented on alternative days with 4 lbs. per head of a natural protein than cows with no protein supplement. Although protein supplementation stimulated extra gain, the cows receiving no protein supplement gained weight and maintained adequate condition for mid-to-late gestation. When quality and quantity of milo stover are satisfactory, satisfactory performance can be achieved by cows in mid-to-late gestation without supplemental protein.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Protein; Milo stubble; Milo stover